Defeasibility of the legal norm that prohibits the application of early termination in crimes against sexual freedom - Cantaro Sanchez, Edgar Johan (2024)
The objective of this article is to identify the legal bases that serve to defeat the rule that regulates the prohibition of early termination in crimes against sexual freedom (third paragraph, article 471 of the Criminal Procedure Code). The need for such an urgent proposal lies in the fact that such a prohibition does not benefit the interests of the victim, but, on the contrary, generates situations of tension, such as: (a) increases the possibilities of re-victimization; (b) generates greater economic costs for the procedural parties, including the victim; (c) promotes untimely justice; and, (d) generates cases of impunity. Therefore, the research will focus on analyzing whether the principle of non-revictimization; the principles of economy and procedural speed; and, effective justice, are necessary foundations to defeat such a norm.